Removable Orthodontic Treatment for Managing Relapse Due to Eruption of Third Molars: A Case Report - Puspitarini Nindya Wardana; Surya Saputra; Chantika Azzahra Anindita Putri; Sekar Hasna Khairunnisa (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2023)
Relapse is a return to the initial form of malocclusion after correction. Relapse occurred after the patient underwent a fixed orthodontic treatment, and it could be associated with the role of third molar eruption. The use of removable orthodontic appliances can maintain the retention period to prevent relapse. This report aims to report the use of removable orthodontic appliances in correcting a minor relapse case. A 23-year-old patient came to RSGM UMY complaining of misaligned upper and lower front teeth for several months after completing fixed orthodontic treatment. She felt her lower front teeth were crowded and moved more backward than the other teeth. The treatment used maxillary and mandibular expansion plates to gain space. The active plate on the maxilla was a medium labial arch and a simple spring on the mandible. A checkup of the patient was seen once a week which involved cleaning the oral cavity and the plate, measuring the space by the activated expansion screw, and checking for correction of individual teeth. The bilateral expansion plate can be used to correct mild anterior crowding due to relapse, followed by an active plate with a simple spring. The success of treatment was influenced by the patient’s cooperation and compliance with using removable orthodontic appliances.